Tax Losses and Excessive Risk Taking under Limited Liability: A Case Study of the TEPCO Bailout after the Fukushima Nuclear Disaster - Nagato, Takayuki (Columbia Journal of Asian Law, 2019)
It is commonly accepted in the tax law literature that, in theory, business tax losses resulting from risk taking should be fully refundable to taxpayers. Further, when such refunds are unrealistic, tax losses should instead be freely transferable or carried forward without time limitations to achieve tax neutrality on risk taking. The general position taken in the literature assumes that such risk taking is socially desirable. However, that assumption does not always hold. For example, the corporate law literature clearly establishes that the rule of limited liability of shareholders encourages corporations to take excessive risks that might harm social welfare. Accordingly, this study theoretically examines the relationship between tax losses and limited liability. Furthermore, this study conducts a case study to empirically demonstrate what kind of tax problem can happen with respect to excessive risk taking. Specifically, the bailout of Tokyo Electric Power Company Holdings (TEPCO) after the Fukushima Dai-ichi nuclear disaster caused by the Great East Japan Earthquake on March 11, 2011, provides an informative case study for a further analysis of this relationship. TEPCO ended up owing over 7.9 trillion yen of compensation liability for the damages caused by its shareholders’ excessive risk taking under limited liability. Although TEPCO’s lack of resources to fully compensate for the damages was easily foreseen, the company did not go into bankruptcy. Instead, the government rescued it without wiping out its existing shareholders. The problem does not end there because the TEPCO bailout created a tax problem. This study questions the appropriateness of allowing TEPCO to deduct its tax losses. This is because TEPCO can circumvent the strict time limitation of the tax loss carryforward period owing to the peculiar legal structure of its bailout scheme. In other words, TEPCO’s existing shareholders, who are assumed to have taken excessive risk can enjoy tax windfall that other corporations’ shareholders cannot. This study considers possible, although imperfect, legislative solutions to the problem.